2023
DOI: 10.1021/acsagscitech.3c00117
|View full text |Cite
|
Sign up to set email alerts
|

Citrate-Stabilized Amorphous Calcium Phosphate Nanoparticles Doped with Micronutrients as a Highly Efficient Nanofertilizer for Environmental Sustainability

Yuriy Sakhno,
Lorenzo Degli Esposti,
Alessio Adamiano
et al.

Abstract: The increase in the global use of phosphorus (P) fertilizers for crop production has generated a series of unintended negative consequences. In response, there is growing interest in developing new fertilizers that curb adverse effects. Among them, amorphous calcium phosphate (ACP) is a viable alternative because of its tunable solubility for P release, high specific surface area, and ability to be doped with vital microelements essential for crops. Herein, we prepared a series of citrate-stabilized ACP nanopa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 46 publications
0
5
0
Order By: Relevance
“…c) The hydroxy group of citrates can interact with phosphate ions and/or d) The phosphate ions can interact with the carboxyl group of citrates (Indurkar et al, 2023b). Previous reports have also shown citrate's efficacy in stabilizing ACP (Chen et al, 2014;Sakhno et al, 2023).…”
Section: Figurementioning
confidence: 99%
“…c) The hydroxy group of citrates can interact with phosphate ions and/or d) The phosphate ions can interact with the carboxyl group of citrates (Indurkar et al, 2023b). Previous reports have also shown citrate's efficacy in stabilizing ACP (Chen et al, 2014;Sakhno et al, 2023).…”
Section: Figurementioning
confidence: 99%
“…Al-Juthery et al [58] discovered nanoamino acids, and nanopotassium increased the nutritional value of wheat by increasing the concentration of essential micronutrients (Zn, Mn, Fe, and Cu) in the grain. Another study by Rahman et al [99] revealed that applying nano-fertilizer resulted in high nutrient use efficiency and significantly improved the nutritional value of tomatoes. Thus, it is imperative to ensure that plants have access to nutrients during their growing cycle to produce food with a high nutritional value and high yield that will meet the nutritional requirements of the population.…”
Section: Nutritional Value Of Nano-fertilizersmentioning
confidence: 99%
“…The improvement of the soil properties resulted in improved water and nutrient retention in the soil and increased the growth parameters of the maize crop compared to the traditional fertilizers. Carmona et al β [99] reported that amorphous calcium phosphate (ACP) demonstrates high solubility compared to nanocrystalline apatite (nAp) and exhibits higher surface reactivity, allowing ACP to have larger nutrient payloads compared to nAp. According to Sakhno et al [100], amorphous calcium phosphate (ACP) has been found to be a viable substitute for conventional fertilizers.…”
Section: Crystalline Structurementioning
confidence: 99%
“…Examples of other papers on nanomaterials relevant for pesticide formulations are as follows: sustainable nanomaterial approaches to essential oil delivery for disease prevention in soy; pesticide formulation processes using polymeric nanoparticles; metal–organic frameworks for controlled release insecticide formulations; utilizing plant virus nanoparticles as delivery vehicles in soil; and bacteria-based nanobiopesticides for plant disease management . Other examples of novel applications that have been published this year are smart gene delivery systems for plants using amine-functionalized carbon dots, nitrogen-doped carbon dots to address drought stress in maize, and nanoparticles doped with micronutrients and P to reduce nutrient leaching to groundwater . The team looks forward to receiving new papers from scientists around the world on sustainable nanomaterial research in 2024.…”
mentioning
confidence: 99%
“…Additional thanks go out to our Editorial Advisory Board members who have provided important guidance and peer reviews and have published their own research this year. The wide range of topics published by our EAB members illustrates their broad expertise ranging from plant science , to soil science and agronomy, sustainable nanomaterials and formulants, ,, pesticide discovery, environmental chemistry, and food safety …”
mentioning
confidence: 99%